Hypoplasia of left pulmonary artery: A rare congenital heart disease - Purani, Charul; Mehariya, K M; Gupta, Kirti; Patel, Priyansi (Indian Journal of Child Health, 2015)
Unilateral hypoplasia or absence of pulmonary artery is a rare pulmonary vascular anomaly that is usually associated with other cardiac anomalies like Tetralogy of Fallot or cardiac septal defects, but can also occur as an isolated anomaly. We present a case of 6-monthold infant who presented with recurrent respiratory tract infection. On work up, chest X-ray showed ipsilateral small hemithorax with hyperluscency in the left lung field. Findings were confirmed with 2D echocardiography and pulmonary angiography which were suggestive of hypoplasia of left pulmonary artery.